San Jose gays in pride parade - Sahl, Ted (photographer):::Creator::::::::::::
Men and women march in a gay pride parade. Two men are holding a long banner with the words "San Jose Gay". Behind them, male and female marchers carry flags with gender symbols denoting same sex relationships: female/female and male/male.